Factors accounting for limited sexual reproduction in a long-lived unisexual plant species - Bisang, Irene; Collart, Flavien; Vanderpoorten, Alain; Hedenäs, Lars (Frontiers in Plant Science, 2025)
IntroductionPlant dispersal directly depends on reproduction success, and hence, on sexual systems. In bryophytes, wherein fertilization involves a continuous film of water between male and female sexual organs, reproduction in unisexual species involves the sympatric distribution of male and female sex-expressing individuals. Here, we determine whether these conditions are controlled by the environment. In particular, we test the hypotheses that (i) sex-expressing males and females exhibit different ecological niches and (ii) environmental variation drives sex expression, sporophyte formation, and hence, dispersal capacities.MethodsWe scored 1,080 specimens of the unisexual moss Abietinella abietina across Sweden as non-sex expressing, expressing female or male, or sporophytic. We tested whether reproductive stages were related to latitude. Topography and climatic conditions at 1-km resolution were employed to measure niche overlap between (i) sex-expressing and non-expressing and (ii) male and female specimens. We finally modelled sex expression and sporophyte production depending on these topo-climatic predictors.ResultsAmong the 63% of reproductive samples across the entire latitudinal gradient, females outnumbered males by a factor 5.6, and 8% of the female samples bore sporophytes. Although the distribution of the sexes was not explained by topo-climatic variables, the probability of sex-expressing samples being male increased with latitude. It resulted in a higher regional sex ratio in the North than in southern regions. Successful sexual reproduction, in terms of sporophyte occurrence, was confined to central Sweden. It was predicted by intermediate to increasing precipitation seasonality and intermediate temperature values.DiscussionDespite a high level of sex-expression, and no significant differences of niche preference between males and females, sporophyte occurrences were rare. Our results suggest that sporophyte formation was determined by mate availability and macro-climatic conditions, the latter possibly affecting fertilization success. We further infer that environmental conditions at the pre-zygotic stage have lower than expected effects on the overall distribution of this moss. Modelling environmental data at higher resolution, smaller scale and expanding geographic coverage to include more sporophyte occurrences, and comparing genetic diversity in sporophytic with non-sporophytic populations, are future lines of this research.